Improved radiosynthesis of 123I-MAPi, an auger theranostic agent - Wilson, Thomas C.; Jannetti, Stephen A.; Guru, Navjot; Pillarsetty, Nagavarakishore; Reiner, Thomas; Pirovano, Giacomo (International journal of radiation biology, 2023)
123 I-MAPi, a novel PARP1-targeted Auger radiotherapeutic has shown promising results in pre-clinical glioma model. Currently, 123 I-MAPi is synthesized using multistep synthesis that results in modest yields and low molar activities (MA) that limits the ability to translate this technology for human studies where high doses are administered. Therefore, new methods are needed to synthesize 123 I-MAPi in high activity yields (AY) and improved MA to facilitate clinical translation and multicenter trials. 123 I-MAPi was prepared in a single step via 123 I-iododetannylation of the corresponding tributylstannane precursor. In vitro internalization assay, subcellular fractionation and confocal microscopy where used to evaluate the performance of 123 I-MAPi in a small cell lung cancer model. 123 I-MAPi was synthesized in a single step from the corresponding stannane precursor in AY of 45 ± 2% and MA of 11.8 ± 4.8 GBq µmol −1 . In vitro in LX22 cells showed rapid internalization (5 min) with accumulation found predominantly in the membrane, nucleus and chromatin of the cell as determined by subcellular fractionation. Here, we have developed an improved radiosynthesis of 123 I-MAPi, an Auger theranostic agent. This process was achieved using a single step, 123 I-iododestannylation reaction from the corresponding stannane precursor in good AY and MA. 123 I-MAPi was evaluated in vitro in a small cell lung cancer model with high PARP expression, rapid internalization and high nuclear uptake shown.